Hubungan Body Mass Index dan Protein Urine Terhadap Kejadian Hipertensi Pada Ibu Hamil Trimester III - Nur Masruroh; Andreas Putro Ragil Santoso; Wildani Thoyyibah; Rindi Anifa Laloda (JIDAN (Jurnal Ilmiah Bidan), 2020)
Background : Hypertension is a complication condition in pregnant women that can cause pre eclampsia. Excess body mass index has the risk of increasing blood pressure. One sign of preeclampsia is thepresence of protein in the urine which is caused by damage to the glomerulus. Objective : to determine the relationship between body mass index and urine protein on the incidence of hypertension in third trimester pregnant women at Prima Husada Hospital Sidoarjo. Methods : This type of research uses quantitative descriptive with cross sectional design Results : there is a relationship between body mass index and the incidence of hypertension in pregnant women with a p value of 0.002. There is no relationship between urine protein and the incidence of hypertension in pregnant women with a p value of 0.270, It is hoped that pregnant women will have regular pregnancy visits for early detection of pregnancy complications